Invisible or fearless: tadpole response to predator cues depends on color. Issue 2 (4th March 2021) - Melo, Gabriela R.; Solé, Mirco; Eterovick, Paula C.
Abstract : Behavioral changes constitute a common response of aquatic animals to predator chemical and/or visual cues. Tadpoles frequently use such signals to evaluate predator presence/activity and, consequently, alter their own behavior to reduce detectability and susceptibility to predation. The present study aimed to test how tadpoles of Bokermannohyla martinsi and Ololygon machadoi respond to the presence of a predator ( Belostoma testaceopallidum ), regarding background choice and activity levels. Results showed that O. machadoi tadpoles increased the use of yellow backgrounds in the presence of the predator perceived through either chemical or visual cues. Bokermannohyla martinsi, on the other hand, did not show preference for any specific background color or changed activity levels in the presence of any predator cue. Our results corroborate the hypothesis of disruptive coloration as a defense strategy in O. machadoi and indicate that the visible and active tadpoles of B. martinsi may employ a different defensive strategy, possibly relying on a more efficient post detection escape mechanism. This hypothesis is corroborated by the higher activity levels of B. martinsi and lack of response to predator presence regarding either modulation of activity levels or background choice.